Techniques of formation dangling anastomosis in stomach surgery - G. Ts. Dambayev; Ch. K. Abilov; V. V. Skidanenko; M. M. Soloviyov; A. N. Baikov; Ye. V. Semichev (Бюллетень сибирской медицины)
The original technique of distal resection of a stomach with formation of a muscular cuff and the hanging down valve from own tissues of a stomach in area of gastroduodenal anasthomosis is offered in article. This allows to avoid development of postgastroresectional complications. Materials of investigations out on 26 experimental mongrel dogs. The results of dynamic observation and instrumental methods of the studies have shown functional full value of the formed anastomosis.